Mutual Recognition of National Minimum Quality Standards may Support International Convergence - Stefan Lutz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
In a model of vertical product differentiation, duopolistic firms face qualitydependent costs and compete in quality and price in two segmented markets. Minimum quality standards, set according to the principle of Mutual Recognition, can be used to increase welfare. The results of the one-shot game suggest that standards achieve initial convergence in terms of qualities produced and national welfares. Therefore, the static game is repeated in multiple periods and firms' qualities in the previous period determine their costs. In an N-period game, quality standards will in fact lead to convergence in terms of qualities and national welfares.
Keywords: F13; F12; L13; 330; product differentiation; oligopoly; trade; quality standards; Produktdifferenzierung; Oligopol; Produktqualität; Normung; Ursprungslandprinzip; Zwei-Länder-Modell; Spieltheorie; Wohlfahrtseffekt; Theorie